Correlational analysis of internal control and inventory management in commercial SMEs of Chimbote - Rodríguez, Ronald Floriano; Chacón, Luis Fernando Espejo; Añazco, Karla Fabrinna Farías; Espinoza, Manuel Eduardo Carrasco; Cutamanca, Héctor Daniel Corcino (Edelweiss Applied Science and Technology, 2024)
The study aims to determine the relationship between internal control and inventory management in micro and small enterprises (SMEs) of Chimbote. A quantitative approach with a correlational design was adopted, and the sample consisted of 160 SMEs, using structured questionnaires on a Likert scale to collect data. Spearman’s Rho coefficient was used to find the levels of association. The results indicated a moderate positive correlation (0.623) between internal control and inventory management, highlighting the importance of dimensions such as the control environment and supervision. However, it was found that only 37.5% of SMEs manage their inventories efficiently, revealing areas for improvement in demand forecasting and inventory policies. In conclusion, strengthening internal control and optimizing inventory management practices are essential strategies for SMEs in Chimbote to optimize their resources, reduce costs, and increase their competitiveness in a globalized and demanding market, thus promoting their sustainability and long-term growth.